2014
DOI: 10.1016/j.neurobiolaging.2013.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cerebrovascular disease and amyloid beta burden on cognition in subjects with subcortical vascular cognitive impairment

Abstract: Cerebrovascular disease (CVD) and amyloid burden are the most frequent pathologies in subjects with cognitive impairment. However, the relationship between CVD, amyloid burden, and cognition are largely unknown. We aimed to evaluate whether CVD (lacunes, white matter hyperintensities, and microbleeds) and amyloid burden (Pittsburgh compound B [PiB] retention ratio) contribute to cognitive impairment independently or interactively. We recruited 136 patients with subcortical vascular cognitive impairment who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
78
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 45 publications
5
78
0
4
Order By: Relevance
“…Although the number of lacunes was associated with performance on tests of both memory and executive function, WMH volume and PiB retention correlated only with memory function. 36 No direct correlation between SVD markers and PiB retention was found, suggesting that the predominant type of SVD is probably perforating arteriolosclerosis in this cohort of patients who had strokes and severe stroke risk factors. A study of hippocampal and cortical thickness of patients with amyloid-negative PET scans derived from this cohort has given further insights into cortical atrophy that might be attributable to arteriolosclerotic SVD rather than Alzheimer's pathology.…”
Section: Molecular Neuroimaging In Other Svd Cohortsmentioning
confidence: 62%
See 1 more Smart Citation
“…Although the number of lacunes was associated with performance on tests of both memory and executive function, WMH volume and PiB retention correlated only with memory function. 36 No direct correlation between SVD markers and PiB retention was found, suggesting that the predominant type of SVD is probably perforating arteriolosclerosis in this cohort of patients who had strokes and severe stroke risk factors. A study of hippocampal and cortical thickness of patients with amyloid-negative PET scans derived from this cohort has given further insights into cortical atrophy that might be attributable to arteriolosclerotic SVD rather than Alzheimer's pathology.…”
Section: Molecular Neuroimaging In Other Svd Cohortsmentioning
confidence: 62%
“…Park et al have looked at the interactions between amyloid burden, MRI markers of SVD, and cognition in a cohort of 136 patients with subcortical vascular cognitive impairment. 36 These older patients with severe vascular risk (hypertension present in >75%), clinical features (all had a focal neurological symptom or sign), and MRI manifestations of severe SVD (mean WMH in mL =38.6±17.1) constitute a unique cohort to evaluate the effects of classical stroke risk factors on VCI. Although the number of lacunes was associated with performance on tests of both memory and executive function, WMH volume and PiB retention correlated only with memory function.…”
Section: Molecular Neuroimaging In Other Svd Cohortsmentioning
confidence: 99%
“…27,28 In fact, a study showed that in patients with subcortical vascular cognitive impairment, the number of lacunes was negatively related with the PiB retention ratio. 29 In patients with recent ischemic stroke, although a relatively increased PiB retention was found in peri-infarct region comparing to the contralateral mirror region, this increased regional PiB retention did not translate into a higher global PiB retention. 30 In experimental stroke models in transgenic mouse with amyloid deposition (APPswe/PS1dE9), increase in new amyloid plaques around the infarcted area was only transient, in which the accumulation most probably reflected an impaired amyloid clearance pathway caused by infarcted tissue.…”
mentioning
confidence: 87%
“…This is supported by a recent study showing that WMH were associated with memory, language, and visuospatial dysfunctions as well as frontal-executive dysfunction. 32 Of note, the topography of decreased nodal efficiency related to WMH relatively spared the medial temporal or precuneus regions. Previous studies have shown that the precuneus is a major hub region in the brain 33 and is involved in the early stage of AD.…”
mentioning
confidence: 99%